Sosialisasi Nugget Sayur Untuk Meningkatkan Konsumsi Sayur Organik Di Kelurahan Sukun Kota Malang - Hayati, Mardiyah; Dewi, Devina Liza Shinta; Lutfiah, Zaidatul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
A healthy lifestyle by eating food and consuming nutritious food has become a new habit for some people. Today, more people are starting to demand organic food, including organic vegetables. One of the preparations that can increase the consumption of organic vegetables is to process vegetables into fast food, namely vegetable nuggets. One of the preparations that can increase the consumption of organic vegetables is to process vegetables into fast food, namely vegetable nuggets. Making vegetarian nuggets from vegetables is a healthy substitute for achieving daily nutritional needs. It is believed that processing vegetables into processed nuggets will attract the attention of consumers, especially children. This product introduction socialization activity was welcomed by PKK mothers of Sukun Village because it had a positive impact, and this discussion raised awareness of nutrition and the benefits of vegetable nuggets. Increase awareness of PKK mothers to choose process.